Educational innovation as a teaching challenge - Medina Uribe, Jury Carla (2021)
Educational innovation brings as a consequence the search for the breaking of the traditional structures that are linked to the educational system, this in order to be able to incorporate knowledge in the process of teaching the formation of students, the main element for these to be changes is in charge of teachers, which falls directly on those processes that are of vital importance for this transformational change, evidencing them through: skills, the application of ICTs, emotional intelligence and hybrid education. Thus, the objective is to carry out the revision of the state of the art of the subject to be treated Educational innovation as a challenge of teaching from a bibliographic search.